The effectiveness of student worksheets based on critical thinking skills in biology class XI high school odd semester - Nasdianur Irawan; Muhammad Zaini; Atiek Winarti (Master Program of Biology Education, Universitas Lambung Mangkurat, Banjarmasin, Indonesia, 2023)
Cognitive skills that are important to note in students are critical thinking skills. Efforts can be made to build students' critical thinking skills through the learning process, supported by innovative teaching materials such as Student Worksheets (SW). This study aims to describe the effectiveness of SW based on critical thinking skills developed in the biology subject of class XI senior high school odd semester. The development stage includes self-evaluation, expert testing, individual testing, small group testing, and field testing. The research subjects were three experts for the validity test, three students for the individual test, seven for the small group test, and 25 for the field test. The effectiveness of SW was analyzed descriptively. The study results showed that the SW developed was stated to be effectively used with effective criteria. Based on these data, the average N-Gain value is 0.53, so the N-Gain category is medium. From the results of this study, it can be concluded that the developed SW based on critical thinking skills in Biology class XI subject matter was effectively used in learning activities.Abstrak Keterampilan kognitif yang penting diperhatikan pada diri peserta didik adalah keterampilan berpikir kritis. Usaha yang dapat dilakukan dalam membangun keterampilan berpikir kritis peserta didik adalah melalui proses pembelajaran, yang didukung oleh penggunaan bahan ajar inovatif seperti Lembar Kerja Peserta Didik (LKPD). Penelitian ini bertujuan mendeskripsikan keefektifan LKPD berbasis keterampilan berpikir kritis yang dikembangkan pada mata pelajaran biologi SMA kelas XI semester ganjil. Tahap pengembangan meliputi evaluasi diri, uji pakar, uji perorangan, uji kelompok kecil, uji lapangan. Subjek penelitian adalah 3 pakar untuk uji validitas, 3 peserta didik untuk uji perorangan, 7 peserta didik untuk uji kelompok kecil dan 25 peserta didik untuk uji lapangan. Keefektifan LKPD dianalisis secara deskriptif. Hasil penelitian menunjukan LKPD yang dikembangkan dinyatakan efektif digunakan dengan kriteria efektif. Berdasarkan data tersebut maka nilai rerata N-Gain 0,53 sehingga diperoleh kategori N-Gain sedang. Dari hasil penelitian ini dapat disimpulkan bahwa LKPD berbasis keterampilan berpikir kritis pada materi pelajaran biologi kelas XI yang dikembangkan efektif digunakan dalam kegiatan pembelajaran.